Does prenatal nicotine exposure alter the brain's response to nicotine in adolescence? A neuroanatomical analysis. Issue 4 (17th May 2013) - Mychasiuk, R.; Muhammad, A.; Carroll, C.; Kolb, B.
Abstract: This study examined changes in dendritic morphology and spine density in multiple brain regions [Zilles' areas: (i) the Cg3 region of the anterior cingulate cortex or the medial prefrontal cortex, layer III (Cg3); (ii) the dorsal agranular insular cortex, layer III (AID); (iii) the PAR I region of the parietal cortex, layer III (Par1) and (iv) the nucleus accumbens (NAc)]of Long–Evans rats following exposure to nicotine prenatally, in late adolescence, or both prenatally and in adolescence. Prenatal nicotine exposure induced enduring changes in neuroanatomical organisation that varied between male and female offspring, with males exhibiting increased dendritic complexity of neurons in AID and NAc whereas females experienced increased dendritic complexity in Par1 but decreased dendritic complexity of neurons in NAc. Similarly, nicotine given in late adolescence dramatically reorganised neural circuitry of both male and female offspring, with males exhibiting decreased dendritic complexity of neurons in Par1 and Cg3 but increased dendritic complexity in AID, and females exhibiting decreased dendritic complexity in Cg3 and NAc but increased complexity in AID. Exposure to nicotine both prenatally and in adolescence produced few neuroanatomical parameters that demonstrated a prenatal experience × adolescent drug administration interaction. Females showed additive effects in Par1, Cg3 and NAc whereas males demonstrated additive effects only in AID. Thus, the timing of nicotine exposure produced differential effects on cerebral organisation in a regionally specific manner. Abstract : Prenatal nicotine exposure has been associated with many negative outcomes including increased risk for nicotine addiction in adulthood. In this study we examined neuroanatomical changes that occurred in response to nicotine exposure in the prenatal period and in adolescence. Although combined exposure to nicotine at both time points was rarely additive; nicotine administration in adolescence profoundly altered neuronal morphology and synaptic plasticity in the brain regions examined.